IMPORTANCE OF CREATIVE METHODS IN HIGHER EDUCATION - Norkulov Bekzod Khurramovich (Western European Studies, 2024)
This article analyzes the importance of creative methods in higher education and teaches attention and progress to them. The article describes the role of creative methods in higher education, their main interest, their application in distance education and their transfer to the system of expansion and movement of education. The article covers the great role of higher education in the use of creative methods in promoting development and innovation.
Keywords: Creativity; Pedagogy; Higher education; Didactics